Diversity, Medicinal and Threatened Plants in Govind Pashu Vihar Wildlife Sanctuary, Western Himalaya - Manikandan, R.; Srivastava, S. K. (Indian Forester, 2015)
The paper deals with information on floristic composition of the Govind Pashu Vihar Wildlife Sanctuary compriseing 821 species, 8 subspecies, 11 varieties and a few cultivated species of Angiosperms, distributed over 479 genera and 125 families, of these, 9 species are critically endangered, 14 species are endangered, 9 species are vulnerable and 7 species are Least Concern. In addition, medicinal plants which form the basis for certain life saving drugs have also been incorporated.